3, 3'-sulfonyldipropionitrile: A novel additive to improve the high temperature performance of lithium-ion battery. (20th February 2015) - Huang, Tao; Zheng, Xiangzhen; Pan, Ying; Wang, Wenguo; Fang, Guihuang; Wu, Maoxiang
Highlights: SDPN used as a cathode film-forming additive. This additive tends to improve cycling performance of the LiMn2 O4 /Li cell (3.0–4.3 V) at 55 °C. A thin SEI with less inorganic degradation products on the surface of electrode using this additive. Abstract: 3, 3'-sulfonyldipropionitrile (SDPN) is structurally different from previously reported compounds and was studied as a film-forming additive for the LiMn2 O4 cathode at elevated temperature. The retention capacity of the LiMn2 O4 /Li cell with the electrolyte (1.0 M LiPF6 –EC/DMC/EMC) containing 0.5 wt% SDPN cycled at 55 °C and increased significantly from 56.7% to 70.3% after 200 cycles. The SDPN is more easily oxidized than the solvents, and may take part in the formation of the interface layeon the cathode surface. The results of electrochemical impedance spectroscopy (EIS) and nuclear magnetic resonance spectroscopy (NMR) show that the solid electrolyte interphase (SEI) is gradually formed during cycling. The X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) data demonstrate that a thinner SEI with less inorganic degradation products can be formed on the surface of the LiMn2 O4 cathode due to SDPN.